PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK MENGGUNAKAN MEDIA GAMBAR DI KELAS 1 - Triana, Triana; Sabri, Tahmid; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is whether an increase in the results of thematic learning by using pictures in class I students of 41 Primary Schools in North Pontianak ?. This type of research is classroom action research. The subjects of the study were students of class I of SD Negeri 41 Pontianak Utara. The research method used is descriptive. Data collection techniques used were direct observation techniques and documentation scrutiny techniques. While the data collection tools are observation sheets and test instruments. The results achieved in this study are (1) the preparation of cycle 1 lesson plans by 2.6 increased in cycle 2 to 2.7 and increased in cycle 3 to 3.0. (2) The increase in the implementation process in cycle 1 was 2.8 increased in cycle 2 to 2.9 and in cycle 3 to 3.0. (3) Learning outcomes also increased from an average of 65.23 in cycle 1 to 80.47 in cycle 2 and increased in cycle 3 to 94.76. Thus, the use of image media in Thematic learning at 41 Primary Schools in North Pontianak can improve student learning outcomes for Class I.Â Keywords:Improvement, learning outcomes, media images